What color is music? Composing polychromatic color harmonies using tonal musical scales - Tari, Gábor (ARTCADIA, 2025)
If the spatial content of two artistically important physical stimuli appears equally in the measurements, or if we can characterize them according to the same criteria, it is natural that we feel the urge to compare them. That is why researchers and artists have been trying for hundreds of years to describe some scientifically correct parallel between colors and musical tones. We also attempt this in this paper, but with the help of a relatively new tool, the digital colorimeter. Since no one has yet developed color harmony guidelines for 7 colors, the creation of color-tones seems to be a great challenge. In Prof. Antal Nemcsics' book, there are also relatively few references to harmonies richer than 4 colors, and he even warns against the mistake of rainbow variegation and rather mentions extended complementary, triad and quadratic harmonies in the color harmony chapter of his book. It is a very mysterious thing and a difficult artistic task to arrange many colors in harmony with each other, as Paul Klee, Amrita Sher Gil or Giorgio Morandi managed, or the kind of color experience we see on the old street facades of buildings in Mediterranean or even Nordic countries without the many colors confusing or shouting each other out. It is completely natural for composers to start writing music in a tonal key in most cases, while painters and designers still do not have such color keys at their disposal, only coloristic clichés – and those too, most of the time inaccurately. This paper tries to fill this gap.
Keywords: color tone; brightness; saturation; polychrome color harmonies; simultaneous contrast